Comparison Between Diffusion‐Weighted MRI and 123I‐mIBG Uptake in Primary High‐Risk Neuroblastoma. Issue 5 (6th December 2020) - Privitera, Laura; Hales, Patrick W.; Musleh, Layla; Morris, Elizabeth; Sizer, Natalie; Barone, Giuseppe; Humphries, Paul; Cross, Kate; Biassoni, Lorenzo; Giuliani, Stefano
Abstract : Background: High‐risk neuroblastoma (HR‐NB) has a variable response to preoperative chemotherapy. It is not possible to differentiate viable vs. nonviable residual tumor before surgery. Purpose: To explore the association between apparent diffusion coefficient (ADC) values from diffusion‐weighted magnetic resonance imaging (DW‐MRI), 123 I‐meta‐iodobenzyl‐guanidine ( 123 I‐mIBG) uptake, and histology before and after chemotherapy. Study Type: Retrospective. Subjects: Forty patients with HR‐NB. Field Strength/Sequence: 1.5T axial DW‐MRI (b = 0, 1000 s/mm 2 ) and T2 ‐weighted sequences. 123 I‐mIBG scintigraphy planar imaging (all patients), with additional 123 I‐mIBG single‐photon emission computed tomography / computerized tomography (SPECT/CT) imaging (15 patients). Assessment: ADC maps and 123 I‐mIBG SPECT/CT images were coregistered to the T2 ‐weighted images. 123 I‐mIBG uptake was normalized with a tumor‐to‐liver count ratio (TLCR). Regions of interest (ROIs) for primary tumor volume and different intratumor subregions were drawn. The lower quartile ADC value (ADC25prc ) was used over the entire tumor volume and the overall level of 123 I‐mIBG uptake was graded into avidity groups. Statistical Tests: Analysis of variance (ANOVA) and linear regression were used to compare ADC and MIBG values before and after treatment. Threshold values to classify tumors as viable/necrotic were obtained using ROC analysis of ADC and TLCR values. Results: No significant difference in whole‐tumor ADC25prc values were found between different 123 I‐mIBG avidity groups pre‐ ( P = 0.31) or postchemotherapy ( P = 0.35). In the "intratumor" analysis, 5/15 patients (prechemotherapy) and 0/14 patients (postchemotherapy) showed a significant correlation between ADC and TLCR values ( P  < 0.05). Increased tumor shrinkage was associated with lower pretreatment tumor ADC25prc values ( P  < 0.001); no association was found with pretreatment 123 I‐mIBG avidity ( P = 0.17). Completely nonviable tumors had significantly lower postchemotherapy ADC25prc values than tumors with >10% viable tumor ( P  < 0.05). Both pre‐ and posttreatment TLCR values were significantly higher in patients with >50% viable tumor than those with 10–50% viable tumor ( P  < 0.05). Data Conclusion: 123 I‐mIBG avidity and ADC values are complementary noninvasive biomarkers of therapeutic response in HR‐NB. Level of Evidence: 4. Technical Efficacy Stage: 3.